Characteristics of Seepage Barriers in Fluvial Reservoirs of Meandering Rivers and Their Impacts on Water Injection Development: A Case Study of Neogene Guantao Formation in Block M, Gudao Oilfield - Ruhao Liu; Yu Sun; Xinrui Wang; Baiquan Yan; Haitao Yu (Geofluids)
To deepen our understanding of reservoir heterogeneity, seepage barriers in the study area were divided into interlayer, intralayer, and planar levels based on their spatial distribution characteristics and then investigated by taking the third member of the Neogene Guantao Formation in the block M of the Gudao oilfield as an example. Based on their genesis characteristics, the interlayer seepage barriers were divided into the overbank sand-overbank sand type, overbank sand-channel type, isolated channel superposition type, and channel shallow-cut type. The planar seepage barriers were categorized into the channel boundary type, abandoned channel type, channel-overbank sand type, and floodplain mudstone type. The intralayer seepage barriers were classified into the mudstone type and physical property type. Classifying multiple levels of different types of seepage barriers led to the refinement of their spatial characteristics. The strength of seepage barriers was characterized using the “seepage barrier coefficient” and “reservoir quality coefficient,” and the small-valued coefficients of the interlayer and intralayer seepage barriers indicated that these seepage barriers are characterized by large thickness, high mudstone content, poor physical properties, and weak seepage ability. The strength of the planar seepage barriers was dependent on the sedimentary facies types and channel stages, and the difference between planar seepage barriers was characterized using the reservoir quality coefficient. The seepage barriers were described based on the multilevel classification of seepage barrier categories, the intralayer seepage barriers with a lateral accretion pattern in the meandering river point bars were identified and described, and the distribution characteristics of seepage barriers were summarized at multiple levels. The method of “hierarchical analysis, skeleton construction, and category fitting” was used to establish 3D models of different levels of seepage barriers, and a modeling method based on the characteristics of intralayer seepage barriers under the constraint of architecture pattern was used to model intralayer seepage barriers with a lateral accretion pattern. In the monitoring of water injection profiles, it was found that the extent of blockage achieved by seepage barriers affects the water injection volume and thus controls the fluid transport pattern. Due to the development characteristics of the seepage barrier in the formation, there are some differences in injection production efficiency under different well pattern matching modes. The research on the distribution characteristics of different levels of seepage barrier categories provides a reliable geological basis for improving the injection-production relationship.